Different pathways of human T-cell activation revealed by PHA-P and PHA-M. - O'Flynn, K; Russul-Saib, M; Ando, I; Wallace, D; Beverley, P; Boylston, A; Linch, D (1986)
Antigen-specific T-cell activation is mediated via the CD3-Ti (antigen receptor) complex, and monoclonal antibodies to both CD3 and Ti cause a rapid rise in intracellular Ca2+. This calcium mobilization is not inhibited by monoclonal antibodies to CD2. The rise in calcium mobilization induced by purified PHA (PHA-P) does not occur in a cell line which lacks CD2 expression, and can be blocked in other T cells by anti-CD2 antibodies. A combination of monoclonal antibodies to different epitopes of CD2 causes calcium mobilization and mitogenesis. Reagent grade PHA (PHA-M) induces calcium moblization in cells that lack CD2, and its effects in other T cells cannot be blocked by anti-CD2 antibodies. The effects of PHA-P and PHA-M are thus mediated predominantly through different activation pathways.